Effect of Power Percentage and Cutting Speed on Tensile Stress Values in Laser Cutting Processes - Sudiro; saputra, onery; Nurharyanto , Anwar (Jurnal INOVATOR, 2023)
This research was conducted to determine the tensile stress of an object that was cut using a laser cutting machine. The purpose of this study is to determine the strength changes in the workpiece caused by cutting using laser cutting based on power and cutting speed. The workpiece used in this study is a polymer type Polymethylmethacrylate (PMMA) or better known as acrylic. This study uses variations in the amount of power and cutting speed, namely 50% power with a cutting speed of 5 mms, 50% power with a cutting speed of 10mms, 70% power with a cutting speed of 5 mms and 70% power with a cutting speed of 10 mms. From the results of tensile stress testing, the amount of power and speed of acrylic cutting affects the tensile stress of the workpiece. The greater the acrylic cutting power will reduce the tensile stress value of the workpiece by 11.4%. The faster the acrylic cutting will reduce the tensile stress value by 10.7%.